Implementasi Kebijakan Pendidikan Berkelanjutan Melalui Kurikulum - Irwan Maulana; Iin Nurul Inayah; Anis Suryaningsih; Ahmad al gufron; Ofik Taufiqurrohman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The sustainable education policy in Indonesia is designed as a response to global challenges such as climate change, social inequality, and technological advancements. This research aims to explain the implementation of sustainable policies in facing various obstacles, including infrastructure limitations, suboptimal curriculum integration, low public awareness, lack of stakeholder collaboration, and the digital divide. This study employs a literature review method, focusing on examining literature related to the implementation of sustainable education policies through the curriculum. Data collection is conducted by gathering literature sources, reading, taking notes, and managing research findings objectively, systematically, analytically, and critically, considering publication years and the most recent studies. The findings of this research indicate the need for improving the quality of sustainable education by focusing on curriculum integration, strengthening infrastructure, increasing public awareness, enhancing cross-sector collaboration, and utilizing technology to expand access to education. With the right strategies, sustainable education is expected to create a generation with high awareness of social, economic, and environmental aspects.